2019
DOI: 10.1007/s11906-019-0983-2
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Leverage Telehealth Approaches Along the Hypertension Control Cascade in Sub-Saharan Africa

Abstract: Purpose of Review: To review current literature on the use of telehealth at different stages of the hypertension control cascade in sub-Saharan Africa (SSA) and to discuss opportunities to harness information and communication technology infrastructure to improve population level hypertension control. Recent findings: There are a limited number of telehealth studies at the different stages of the hypertension control cascade. The small body of evidence suggests several promising innovations. These innovations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Out of the fourteen unique studies included in this review, the majority (n = 11) demonstrated a significant improvement in either systolic or diastolic blood pressure, and two studies showed a non-significant improvement in either systolic blood pressure, diastolic blood pressure, or percentage of participants who achieved target blood pressure levels. Indeed, the broader literature on mobile health applications for NCD management in LMICs has generally shown promise for improving clinical outcomes, and our results contribute to the existing literature through demonstrating an overall positive impact of telemedicine for hypertension management [10][11][12]33]. Eight of the nine studies that investigated interventions to improve patient medical management displayed significant reductions in blood pressure, whereas only three of the five studies that assessed interventions to modify behavioral risk factors reported significant changes.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Out of the fourteen unique studies included in this review, the majority (n = 11) demonstrated a significant improvement in either systolic or diastolic blood pressure, and two studies showed a non-significant improvement in either systolic blood pressure, diastolic blood pressure, or percentage of participants who achieved target blood pressure levels. Indeed, the broader literature on mobile health applications for NCD management in LMICs has generally shown promise for improving clinical outcomes, and our results contribute to the existing literature through demonstrating an overall positive impact of telemedicine for hypertension management [10][11][12]33]. Eight of the nine studies that investigated interventions to improve patient medical management displayed significant reductions in blood pressure, whereas only three of the five studies that assessed interventions to modify behavioral risk factors reported significant changes.…”
Section: Discussionmentioning
confidence: 50%
“…Telemedicine has the potential to reduce barriers to primary healthcare in LMICs, including transportation burden, overcrowded facilities, and healthcare workforce shortages [9]. While several studies have investigated the scope of telehealth and mobile services for NCD management in LMICs, many of these reviews assessed technology platforms for oneway communication such as unidirectional text messaging or automated patient reminders [10][11][12]. To our knowledge, there are few studies specifically evaluating telemedicine applications involving direct communication between healthcare providers or between providers and patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the proportion of caregivers who reported using a mobile phone (85%) was similar to the national mobile phone subscription rate in Tanzania (82%) [ 13 ]. In sub-Saharan Africa, data plans are often inexpensive, and their use is widespread regardless of socioeconomic status [ 22 , 23 ]. Furthermore, investments in mobile phone infrastructure have led to an estimated 93.7% cell tower coverage nationwide, suggesting that an intervention delivered by mobile phone has a high potential reach in Tanzania [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remote interventions enable access to medical services by people who have onerous conditions that limit their ability to go to face-to-face appointments, for reasons of disease limitation (PB5), age or living in locations distant from medical centers. In addition, digital health through smartphones, increasingly widespread among the low-income public, is an alternative for meeting the needs of low-income people, who do not always have access to health information and quality medical care (Muiruri et al, 2019). Still referring to the low-income population, remote interventions would avoid having to take time off work for in-person consultations, an option not always feasible for this public (Kelso & Feagins, 2018).…”
Section: Personal Subsystemmentioning
confidence: 99%